2016
DOI: 10.1371/journal.pone.0151233
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine and Glycine Differentially Control Neurotransmission during Visual Cortex Critical Period

Abstract: N-methyl-D-aspartate receptors (NMDARs) play a central role in synaptic plasticity. Their activation requires the binding of both glutamate and d-serine or glycine as co-agonist. The prevalence of either co-agonist on NMDA-receptor function differs between brain regions and remains undetermined in the visual cortex (VC) at the critical period of postnatal development. Here, we therefore investigated the regulatory role that d-serine and/or glycine may exert on NMDARs function and on synaptic plasticity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Furthermore, they demonstrated that there was a close correspondence in the expression of SR, NMDAR, especially glutamate, glycine, and PCP binding sites, and D‐serine levels in the forebrain and an inverse association in DAAO expression and D‐serine levels in the cerebellum and hindbrain where glycine was found in high concentrations . Thus, they concluded that D‐serine is the primary co‐agonist at synaptic NMDAR in the forebrain . They succeeded in the purification and characterization of SR from the rat brain in 1999 .…”
Section: Pathophysiological Role Of Serine Racemase and D‐serinementioning
confidence: 99%
“…Furthermore, they demonstrated that there was a close correspondence in the expression of SR, NMDAR, especially glutamate, glycine, and PCP binding sites, and D‐serine levels in the forebrain and an inverse association in DAAO expression and D‐serine levels in the cerebellum and hindbrain where glycine was found in high concentrations . Thus, they concluded that D‐serine is the primary co‐agonist at synaptic NMDAR in the forebrain . They succeeded in the purification and characterization of SR from the rat brain in 1999 .…”
Section: Pathophysiological Role Of Serine Racemase and D‐serinementioning
confidence: 99%
“…The actual real specificity of these compounds remains unknown and could display unwanted off-target effects as illustrated for OHAsp, PES and PM, which have been largely used to inhibit SR [42][43][44][45][46][47][48] Therefore, the specificity of a putative inhibitor has to be first validated in SR −/− or DAAO −/− mice, depending on the target of the compound. The actual real specificity of these compounds remains unknown and could display unwanted off-target effects as illustrated for OHAsp, PES and PM, which have been largely used to inhibit SR [42][43][44][45][46][47][48] Therefore, the specificity of a putative inhibitor has to be first validated in SR −/− or DAAO −/− mice, depending on the target of the compound.…”
Section: Pharmacological Inhibition Of D-serine Function and Metabolimentioning
confidence: 99%
“…Thus, it has been reported that OHAsp introduced in the astrocytes impaired LTP recorded in hippocampal slices although no rundown in glutamatergic responses was observed 42 or reduced NMDA-excitatory postsynaptic currents (EPSCs)-EPSCs recorded at layer 5 pyramidal neurons, 44 effects that could be fully rescued by adding D-serine back to tissues. 47 Application of PES and PMS to neonatal mouse cerebellum slices impedes neuronal migration 48 and also decreases respiratory frequency when applied to brainstem slices. Using bath application, PES was found to reduce light-evoked NMDAR response in the retina, 46 or the EPSCs and LTP in the visual cortex.…”
Section: Off-target Effects Of Some Genetic and Pharmacological Toomentioning
confidence: 99%
See 2 more Smart Citations